Academic dishonesty and Chat GPT - Mohd Zani, Amirudin; Setia, Roszainora (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Academic dishonesty refers to any behavior that undermines the integrity of the academic process, such as plagiarism, cheating, and data fabrication (Holden et al., 2021). One of the main challenges in clearly defining academi dishonesty is the existence of numerous cheating behaviors. Academic dishonesty can range from using concealed notes during a closed-book exam to copying a friend's assignment or even hiring third-party companies to write papers, prepare case reports, or obtain past versions of exams (Mukhtar et al., 2020).